Integração e relações bilaterais assimétricas : Brasil-Guyana e Brasil-Suriname - Lima, Suely Aparecida de (2017)
Guyana and Suriname are small countries facing up to difficulties of insertion in South America. For this reason, a profile for their asymmetric bilateral relations with Brazil was drawn through the articulation of binomial integration-asymmetry. Brantly Womack’s theory of asymmetry was approached as a theoretical-methodological resource for this research. With regard internal asymmetries common to the three countries concerned, there is a conformation between ethnic-racial and regional asymmetries marked by lack of infrastructure. In relation to asymmetries between Brazil and Guyana and Brazil and Suriname, the South American panorama indicates that Brazil’s advantages over Guyana and Suriname are relative, not absolute. Their differences in capacity can be transformed and negotiated. Nonetheless, transformation is conditioned to broader structures and conjunctures. On the other hand, negotiation is available to asymmetric pairs with a propensity for cooperation, which is the case of these bilateral relations in question. In this context, while Guyana and Suriname use their relative and natural advantages, Brazil provides a wider framework to address themes that permeate such bilateral relations in the official sphere. Examples of this are the incorporation of technical cooperation by the Brazilian Cooperation Agency (Agência Brasileira de Cooperação - ABC); bilateral trade by the Program of Competitive Import Substitution (Programa de Substituição Competitiva de Importações – PSCI) and; physical integration by the Iniciative for the Integration of the Regional Infrastructure of South America (Iniciativa para a Integração da Infraestrutura Regional Sul-Americana – IIRSA)/South American Council of Infrastructure and Planning (Conselho Sul-Americano de Infraestrutura e Planejamento – COSIPLAN)/Union of South American Nations (União das Nações Sul-Americanas – UNASUL). As a result, this Brazilian strategy turns essentially political issues into technical concerns.